Photons as a 21st century reagent - Holly E. Bonfield (Nature Portfolio, 2020)
A pharmaceutical industry viewpoint on how the fundamental laws of photochemistry are used to identify the parameters required to implement photochemistry from lab to scale. Parameters such as photon stoichiometry and light intensity are highlighted within to inform future publications.